CULTURAL AND LINGUISTIC PICTURE OF THE WORLD: SIMILARITIES AND DIFFERENCES - Tursunova M. E. (Bright Mind Publishing, 2025)
This study explores the concept of the cultural and linguistic picture of the world, analyzing both universal patterns and cross-cultural variations. Drawing on cognitive linguistics, sociolinguistics, and cross-cultural studies, the research examines how language encodes cultural knowledge and reflects cognitive processes. The paper compares linguistic categories, metaphors, and semantic fields across languages, highlighting both convergences and divergences. Findings indicate that while human cognition generates universal conceptual structures, linguistic and cultural frameworks influence perception and expression differently. This article contributes to the understanding of the interplay between language, thought, and culture, offering implications for intercultural communication and language teaching.
Keywords: Cultural world view, linguistic relativity, cross-cultural comparison, cognitive linguistics, semantic categories.